STUDI MORFOANATOMI GONAD DAN FEKUNDITAS IKAN NILEM (Osteochilus vittatus) DENGAN PAKAN SUPLEMENTASI TEPUNG SPIRULINA - Rijal, Muhammad Azharul; Pratama, Ikhsan; Susanto, Susanto; Agung, Rendi Marta (Universitas Mataram, 2025)
Nilem fish (Osteochilus vittatus) is a fish native to eastern Indonesia. People in general like nilem fish due to many factors. The demand for nilem fish increases every year. This increase in demand must be accompanied by an increase in reproductive performance so that the stock of nilem fish is always maintained. Reproduction is the ability of an individual to produce offspring. There are several factors that greatly influence reproductive success, including environmental factors and food. Food content that is high in protein can improve fish reproductive performance. Spirulina platensis is a type of blue green algae that can live in fresh and brackish waters. The content of macromolecules and micromolecules in spirulina is very high. The protein contained in spirulina ranges from 55-65%, 5-7% fat, while the micromolecules contain 6-13% amino acids, 5% minerals. This research was conducted using a completely randomized design method with four treatments and four replications. The results of this research are that the addition of spirulina flour has a good effect on the morphoanatomical response of nilem fish. Giving spirulina flour had a real effect on GSI, HSI and fish weight, while fish length, fecundity and VSI had no real effect. The optimum dose in this study was P2 30g spirulina flour in 1 kg fish feed. Based on this research, feeding spirulina supplementation can increase the reproductive response of nilem fish